2018
DOI: 10.1021/acs.nanolett.7b04385
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Induced Magnetic Resonance Enhanced Raman Spectroscopy

Abstract: Plasmon-induced magnetic resonance has shown great potentials in optical metamaterials, chemical (bio)-sensing, and surface-enhanced spectroscopies. Here, we have theoretically and experimentally revealed (1) a correspondence of the strongest near-field response to the far-field scattering valley and (2) a significant improvement in Raman signals of probing molecules by the plasmon-induced magnetic resonance. These revelations are accomplished by designing a simple and practical metallic nanoparticle-film plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 42 publications
1
67
0
Order By: Relevance
“…Therefore, SPP‐LSP coupling efficiency is given as α = G SPP & LSP /( G SPP * G LSP ) ≈ 0.126. Besides, SPP‐LSP coupling also exists in the nanogap between grating surface and Au nanospheres, which was caused by plasmon‐induced magnetic resonance . As shown in Figure a, the electric field intensity within the nanogap, between the grating surface and Au nanospheres | E LSP & SPP | 2 ≈ 52900| E 0 | 2 ( G LSP&SPP = 230).…”
Section: Spp‐lsp Coupling Characteristics Of 2d Ag Sinusoidal Nanogramentioning
confidence: 99%
“…Therefore, SPP‐LSP coupling efficiency is given as α = G SPP & LSP /( G SPP * G LSP ) ≈ 0.126. Besides, SPP‐LSP coupling also exists in the nanogap between grating surface and Au nanospheres, which was caused by plasmon‐induced magnetic resonance . As shown in Figure a, the electric field intensity within the nanogap, between the grating surface and Au nanospheres | E LSP & SPP | 2 ≈ 52900| E 0 | 2 ( G LSP&SPP = 230).…”
Section: Spp‐lsp Coupling Characteristics Of 2d Ag Sinusoidal Nanogramentioning
confidence: 99%
“…Based on these observations, we emphasize that the magnetic mode in the nanosphere DoFN has quite different resonant features to that of a nanosphere MoFN as reported before. [46] In a nanosphere MoFN with large sphere, the magnetic dipolar mode can form due to the excitation of confined displacement current loop around the gap between the particle and the film. As a re-sult, the magnetic "hot spot" resides in the gap region between the particle and the film.…”
Section: Numerical Investigation Of Plasmon-induced Optical Magnetismmentioning
confidence: 99%
“…[40][41][42][43][44][45] Recently, Chen et al showed that an optical magnetic resonance can also be realized in a nanosphere MoFN, provided that the nanosphere diameter is large enough. [46] The magnetic resonance in such a nanosphere MoFN is produced essentially by the displacement current loop that is tightly squeezed in the nanometer-thick particle-film gap. This work indicates that even for the simplest nanosphere MoFN system, plasmonic near-field coupling between the particle and the metal film is capable of producing rich plasmon modes of both electric and magnetic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperbolic meta-molecules were also proved to enable an arbitrary control of scattering and absorption of light through the excitation of magnetic resonances, which offer a superior sensitivity and field enhancement, compared with the more conventional electric resonances [178]. It is worth mentioning that optical magnetism is an active research field, since magnetic resonances have been proved to provide a new degree of freedom for nanostructured systems, which can trigger unconventional nanophotonic processes, such as nonlinear effects [179] or electromagnetic field localization for enhanced spectroscopy [ 180] and optical trapping [ 181,182] (for more details, see the reviews by Calandrini et al [183] and by Urzhumov and Shvets [184]). Important efforts have been spent in the development of metamaterials due to the difficulty to induce strong magnetic effects at optical frequencies by using natural materials or conventional plasmonic architectures.…”
Section: Artificial Optical-magnetism In Coupled Plasmonic Metamaterialsmentioning
confidence: 99%